2014
DOI: 10.1248/bpb.b13-00989
|View full text |Cite
|
Sign up to set email alerts
|

St. John’s Wort Promotes Adipocyte Differentiation and Modulates NF-κB Activation in 3T3-L1 Cells

Abstract: St. John's wort (SJW), or Hypericum perforatum, is a perennial herb that has been used in the treatment of depression in several countries. Though its therapeutic effect on depression has been extensively studied, its influence on metabolic syndrome is yet to be fully characterized. Therefore, we investigated the effect of SJW extract on adipocyte differentiation and its anti-inflammatory effects by using 3T3-L1 preadipocytes. Oil Red O staining indicated that SJW promotes adipocyte differentiation, while immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
2
18
0
1
Order By: Relevance
“…3 Indeed, NF-κB has a pivotal role in the regulation of many genes responsible for the generation of mediators in Our results showed marked decline of renal NF-кB expression in HP treated groups. Similar findings were obtained by Hatano et al 37 who showed the ability of HP in reducing NF-кB expression in rat with metabolic syndrome. Furthermore, our results showed that HP caused dose-dependent reductions of the elevated levels of TNFα and IL-1β in the kidney of HP treated groups.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…3 Indeed, NF-κB has a pivotal role in the regulation of many genes responsible for the generation of mediators in Our results showed marked decline of renal NF-кB expression in HP treated groups. Similar findings were obtained by Hatano et al 37 who showed the ability of HP in reducing NF-кB expression in rat with metabolic syndrome. Furthermore, our results showed that HP caused dose-dependent reductions of the elevated levels of TNFα and IL-1β in the kidney of HP treated groups.…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed marked decline of renal NF‐кB expression in HP treated groups. Similar findings were obtained by Hatano et al . who showed the ability of HP in reducing NF‐кB expression in rat with metabolic syndrome.…”
Section: Discussionsupporting
confidence: 90%
“…Both fish oil (123) and omega-3 (124,125) supplementation increased adiponectin levels in human studies. St. John's Wort (Hypericum perforatum) (126) and Groundsel Bush (Baccharis halimifolia) extract (127) induce 3T3-L1 adipocyte differentiation leading to enhanced adiponectin expression. Additional supplements that have been shown to increase circulating adiponectin in humans and animals include grape-seed extract (128-130) green tea extract (131,132), walnuts (133,134), α-linolenic acid (135), resveratrol (136)(137)(138), and Radix Astragali isolated compounds (astragaloside II and isoastragaloside I) (139).…”
Section: Increase Circulating or Local Levelsmentioning
confidence: 99%
“…There were discrepancies between these findings and those of similar in vitro studies. Notably, 50 µg/mL of SJW extract was used in our study [38] which was a slightly higher concentration than that used in previous in vitro reports [36,37], suggesting that the content and/or concentration of the bioactive ingredients in our SJW extract possibly differed from those used in other studies. The differences in the ingredients might be responsible for the varying study results.…”
Section: Effects Of Sjw On Differentiation Of Adipocytes and Secretiomentioning
confidence: 72%
“…Concentrations of extract in the range of 25-50 µg/mL were used for the experiments. Commercially available extracts from the flower tops of SJW have also been investigated [38]. In our study, treatment of 3T3-L1 cells with SJW extract facilitated differentiation of adipocytes without cell hypertrophy and increased the expression and secretion of adiponectin.…”
Section: Effects Of Sjw On Differentiation Of Adipocytes and Secretiomentioning
confidence: 75%